Impersonal use of "tú"and "uno" in the Spanish spoken in Caracas and other cities. - Guirado, Krístel (Círculo de Lingüística Aplicada a la Comunicación, 2012)
Pronouns tú y uno (you and one) can be used to express the indeterminacy of the subject in Spanish. Research about subject pronouns shows that the non-specific tú is more frequent in some dialects than others. Cameron (1993) and DeMello (2000) attempt to explain these differences, but their assumptions are questionable. In this study, analyze the alternation tú~uno (you~one) in impersonal sentences is analyzed in a speech sample of Caracas, recorded in 1987 with the purpose of comparing the results with data from other Spanish-speaking communities. Also, the differences of both pronouns in the different varieties of Spanish are explained. The results show that speakers from Caracas prefer uno (one) instead of tú (you) to express semantic impersonality. Moreover, the opposition tuteo vs. ustedeo appears to be a viable hypothesis to explain the nature of the observed dialect differences.
Keywords: Spanish pronouns tú~uno; Caracas; semantic impersonality; dialectal variation.